Civil Liability of Medical Team Members A Comparative Study - Ali Jaleel, Researcher. Islam; Siwan Atwan, Prof. Dr. Raed (Basra studies journal, 2024)
Treating a patient by a medical team inherently involves several individuals. If the patient suffers harm, it’s likely that each member of the medical team has contributed to it in some way. Therefore, responsibility must be distributed among them, either equally or unevenly depending on each one’s contribution to the harm. If the patient contracting with the medical team is to benefit from guaranteeing his right, by agreeing to solidarity among the medical team, then this agreement has no place in tort liability. This is because the injured party usually cannot foresee the damages that may befall him in advance, so he resorts to agreeing on them by making solidarity among the members of the medical team about the damage. The contractual relationship may exist between the patient and some members of the medical team, while tort liability governs other relationships. These relationships result in harm to the patient and are then questioned in terms of solidarity, not joint liability.